A dual-texture corrosion-resistant magnesium alloy material and preparation method thereof

By adopting a dual-textured process in the magnesium alloy material, the alloy powders with high Sn, Zn and RE elements are laid at different levels of the mold cavity, and undergoing multi-step process processing, the problem of difficult to take into account both the corrosion resistance and toughness of magnesium alloy materials is solved, and the preparation of magnesium alloy materials with high corrosion resistance and high strength and toughness is achieved.

CN115870497BActive Publication Date: 2025-03-04HUNAN INSTITUTE OF ENGINEERING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211526571.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-03-04
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

It is difficult to take into account the corrosion resistance and toughness of existing magnesium alloy materials, and it is difficult to obtain a cylinder texture with high corrosion resistance in conventional processes.

Method used

By laying high Sn content magnesium alloy powder, high Zn content magnesium alloy powder and high RE content magnesium alloy powder respectively on the outer layer, transition layer and inner layer of the cylindrical mold cavity, and undergoing molding, vacuum hot press sintering, extrusion deformation, rolling deformation and annealing heat treatment, a double-textured corrosion-resistant magnesium alloy material was prepared.

Benefits of technology

It realizes the comprehensive mechanical properties of high corrosion resistance and high strength and toughness of magnesium alloy materials, and can meet the engineering application needs of aerospace, transportation and 3C communication and electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115870497B_ABST
    Figure CN115870497B_ABST
Patent Text Reader

Abstract

The present invention relates to a dual-texture corrosion-resistant magnesium alloy material and a preparation method thereof, and belongs to the technical field of nonferrous metal material preparation. According to the method, high tin (Sn) content magnesium alloy powder, high zinc (Zn) content magnesium alloy powder, and high rare earth (RE) content magnesium alloy powder are laid on the outer layer, transition layer, and inner layer of a cylindrical mold cavity respectively, and through molding, vacuum hot pressing sintering, extrusion and rolling deformation, and annealing heat treatment, a dual-texture corrosion-resistant magnesium alloy material with a cylindrical texture on the outer layer and a rare earth texture on the inner layer can be obtained. The prepared magnesium alloy material has the characteristics of dual textures of inner and outer layers, and has the advantages of high corrosion resistance and high strength and toughness comprehensive mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metal material preparation, and in particular relates to a double-texture corrosion-resistant magnesium alloy material and a preparation method thereof. Background Art

[0002] As a green engineering material in the 21st century, magnesium alloy has a series of advantages such as low specific gravity, good damping and shock absorption effect, and good electromagnetic shielding performance. It has received more and more attention in aerospace, transportation, 3C communication and electronic products. However, due to the low electrode potential of magnesium, the magnesium oxide film is brittle and not dense, which leads to poor corrosion resistance. Poor corrosion resistance is one of the important reasons that currently restrict the large-scale engineering application of magnesium alloys.

[0003] Studies have shown that the corrosion resistance of magnesium alloys is closely related to factors such as composition and texture. Only adding tin (Sn) or rare earth (RE) elements to magnesium alloys can obtain better corrosion resistance than conventional AZ magnesium alloys. Adding an appropriate amount of Sn elements can significantly improve the corrosion resistance of magnesium alloys, but it is easy to form a strong base surface texture after conventional plastic deformation, resulting in poor room temperature plasticity of the alloy; while adding only RE elements can obtain good corrosion resistance and rare earth texture, and also have good room temperature plasticity, but the yield strength of the alloy is low, which is difficult to meet the mechanical properties requirements of engineering components. In addition, the addition of RE leads to high material costs, which is not conducive to engineering applications. Further, when Sn and RE elements are added to magnesium at the same time, due to the strong affinity between Sn and RE atoms, a large number of fireworks-like MgSnRE ternary brittle phases are generated by reaction. These second phases will act as micro-anodes, aggravating the galvanic corrosion of the magnesium alloy matrix, and ultimately resulting in low corrosion resistance of the alloy, and also poor mechanical properties such as alloy plasticity and strength. Therefore, it is difficult for existing methods to achieve the advantages of high corrosion resistance and high toughness mechanical properties under the conditions of adding Sn or RE elements. In addition, texture also has an important influence on the corrosion resistance of magnesium alloys. Studies have shown that the corrosion resistance of magnesium prisms

[0004] The corrosion resistance of the sample with cylindrical texture is better than that of the sample with basal texture in AZ series magnesium alloys. However, magnesium alloys are prone to form strong basal textures after conventional extrusion or rolling deformation processes, and it is difficult to obtain cylindrical textures, which cannot improve the corrosion resistance of magnesium alloys. Therefore, how to make full use of the low-cost Sn to replace RE and prepare magnesium alloy materials with high corrosion resistance, high strength and toughness and comprehensive mechanical properties is of great significance to fully utilize my country's magnesium resource advantages and expand its engineering applications. It is also a key technical problem that needs to be solved in the development of high-strength, toughness and high corrosion resistance magnesium alloys. Summary of the invention

[0005] Based on this, the present invention provides a dual-texture corrosion-resistant magnesium alloy material and a preparation method thereof.

[0006] The specific content of the invention is as follows:

[0007] A dual-texture corrosion-resistant magnesium alloy material and a preparation method thereof include the following steps: providing the raw materials for preparing the material: high Sn content magnesium alloy powder, high Zn content magnesium alloy powder, high RE content magnesium alloy powder;

[0008] The high Sn content magnesium alloy powder, high Zn content magnesium alloy powder, and high RE content magnesium alloy powder are laid on the outer layer, transition layer, and inner layer of a cylindrical mold cavity, respectively, and the dual-texture corrosion-resistant magnesium alloy material is obtained through molding, vacuum hot pressing sintering, extrusion deformation, and annealing heat treatment.

[0009] It is worth mentioning that the reason for arranging the high Sn content magnesium alloy powder in the outer layer is that the solid solubility of Sn in magnesium is large, and no large second phase will be formed, thus avoiding the galvanic corrosion effect caused by the large second phase. In addition, due to the difference in stacking fault energy, twin deformation is prone to occur in Mg-Sn alloys, and cylindrical texture can be obtained by regulating the extrusion and rolling processes; while the solid solubility of RE in magnesium varies greatly with the type of element, and rare earth texture is easy to obtain after extrusion or rolling deformation, but it is difficult to obtain cylindrical texture through the regulation process, so it is not conducive to the improvement of corrosion resistance. In addition, the heterogeneous structure layout mode with strong outer and tough inner can synergistically improve the strength and toughness of magnesium alloy materials.

[0010] Preferably, the composition of the high Sn content magnesium alloy powder is as follows, in parts by mass:

[0011] Mg-(5-7wt.%)Sn alloy powder 70-90 parts;

[0012] 10 to 30 parts of Mg-(2-4wt.%)Zn alloy powder.

[0013] Preferably, the composition of the high Zn content magnesium alloy powder is as follows, in parts by mass:

[0014] Mg-(2-4wt.%)Zn alloy powder 80-90 parts;

[0015] 10 to 20 parts of Mg-15wt.%Mn alloy powder.

[0016] Preferably, the composition of the high RE content magnesium alloy powder is as follows, in parts by mass:

[0017] 25-45 parts of Mg-(2-4wt.%)Zn alloy powder;

[0018] Mg-(1.5-3wt.%)RE alloy powder 50-70 parts;

[0019] 1 to 5 parts of Mg-15wt.%Mn alloy powder.

[0020] It is worth mentioning that in order to avoid the formation of large-sized Mg2Sn phase or MgZn phase between the laying positions of the high Sn content magnesium alloy powder and the high Zn content magnesium alloy powder, and the formation of large LPSO phases between the laying positions of the high Zn content magnesium alloy powder and the high RE content magnesium alloy powder, pure magnesium foil is added at the above-mentioned powder interface. Adding magnesium foil can regulate the chemical composition gradient of the interface, inhibit the formation of large second phases, and withstand greater deformation pressure during subsequent pre-pressing and vacuum hot pressing sintering to promote the nucleation rate of recrystallization to obtain a smaller grain size and a finely dispersed second phase, thereby achieving an increase in the bonding strength between the interfaces. In addition, considering the high strength and toughness requirements of subsequent magnesium alloy materials, the thickness of the magnesium foil should not be too thick to avoid reducing the strengthening effect. Further preferably, the foil thickness is 0.3-0.8mm.

[0021] Further preferably, the radial width of the magnesium alloy powder with high Sn content is 20-40 mm, the radial width of the magnesium alloy powder with high Zn content is 3-10 mm, and the radial width of the magnesium alloy powder with high RE content is 40-100 mm.

[0022] Preferably, the RE is one or more of Gd, Ce, La, Nd, and Y.

[0023] More preferably, the molding pressure is 60 MPa to 100 MPa.

[0024] It is worth mentioning that in order to prevent the magnesium alloy from being oxidized at high temperatures, the hot pressing sintering process is carried out in a vacuum; at the same time, the addition of Sn or RE elements to magnesium will improve the heat resistance of the magnesium alloy. In order to improve the bonding strength of the material after sintering, the powder blank after demolding is subjected to vacuum hot pressing sintering. Preferably, the vacuum hot pressing sintering temperature is 480℃~550℃, the time is 2~3 hours, and the pressure is 10~50MPa.

[0025] It is worth mentioning that in order to further refine the grain size of the sintered magnesium alloy material and improve the density, and also to obtain a specific texture and high-strength and toughness mechanical properties, preferably, the extrusion deformation temperature is 250°C to 400°C, and the extrusion ratio is 5 to 15.

[0026] Furthermore, in order to regulate the texture of the material surface, a low deformation rolling deformation process is used to generate a large number of tensile twins in the hot extrusion recrystallization structure. The interaction between twins and dislocation slip induces a recovery process to obtain micro-nano structures such as subgrains, which then become nucleation points for static recrystallization in subsequent annealing. Since the tensile twins and the parent grains form an angle difference of about 86°, a cylindrical texture component different from the extruded strong base surface texture is obtained. In addition, a large number of twin boundaries and the dispersed Mg2Sn phase can further regulate the morphology, orientation and size of the phase. Due to the cylindrical texture in the magnesium alloy and the micro-nano structure of the fine and uniform second phase, the corrosion resistance is better. Furthermore, due to the small amount of cold rolling deformation, a strain gradient will appear from the outer layer to the inner layer of the material, and the deformation of the inner layer is very small, which will hardly affect the toughness structure and rare earth texture of the layer, so that a dual-texture magnesium alloy material with cylindrical texture in the outer layer and rare earth texture characteristics in the inner layer can be obtained. Preferably, the rolling deformation temperature is 20° C. to 100° C., the rolling deformation amount is 5% to 10%, and the rolling direction is parallel to the extrusion direction.

[0027] More preferably, the annealing heat treatment is performed at a temperature of 200° C. to 350° C. and for a time of 30 to 240 min.

[0028] In addition, the present application also provides a dual-texture corrosion-resistant magnesium alloy material produced by the above method.

[0029] The above-mentioned dual-texture corrosion-resistant magnesium alloy material and its preparation method are to lay high Sn content magnesium alloy powder, high Zn content magnesium alloy powder, and high RE content magnesium alloy powder on the outer layer, transition layer and inner layer of the cylindrical mold cavity respectively, and then through molding, vacuum hot pressing sintering, extrusion and rolling deformation, annealing heat treatment, the dual-texture corrosion-resistant magnesium alloy material can be obtained. The outer layer is prepared by high Sn content magnesium alloy powder, and after process control, cylindrical texture and high corrosion resistance can be obtained. The inner layer is prepared by high RE content magnesium alloy powder, and rare earth texture and high strength and toughness can be obtained; the transition layer is prepared by high Zn content magnesium alloy powder between the inner and outer layers, which can effectively avoid the formation of brittle MgSnRE ternary phase at the interface of the inner and outer layers, and realize reliable metallurgical bonding. The prepared magnesium alloy material has the characteristics of dual texture of inner and outer layers, high corrosion resistance, and the advantages of heterogeneous structure with strong outer and tough inner. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the process flow of the present invention;

[0031] Figure 2 The texture of the inner and outer layers and the phase distribution at the interface of Example 1 of the present invention;

[0032] Figure 3 This is the second phase cracking phenomenon at the interface of the inner and outer layers of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] It should be noted that the dual-texture corrosion-resistant magnesium alloy material in the present application includes an outer layer, an inner layer and a transition layer connecting the inner and outer layers.

[0036] A method for preparing a dual-texture corrosion-resistant magnesium alloy material according to one embodiment comprises the following steps:

[0037] Step 1: Provide raw materials for preparing the outer layer of the material: high Sn content magnesium alloy powder.

[0038] The high Sn content magnesium alloy powder includes 70-90 parts by mass of Mg-(5-7wt.%) Sn alloy powder and 10-30 parts by mass of Mg-(2-4wt.%) Zn alloy powder.

[0039] It should be noted that Mg-(5-7wt.%)Sn alloy powder refers to an alloy powder in which the mass content of Sn is 5% to 7%, and the balance is Mg. Mg-(2-4wt.%)Zn alloy powder refers to an alloy powder in which the mass content of Zn is 2% to 4%, and the balance is Mg.

[0040] Step 2: Providing raw materials for preparing the inner layer of the material: high RE content magnesium alloy powder.

[0041] The high RE content magnesium alloy powder includes 25-45 parts by mass of Mg-(2-4wt.%) Zn alloy powder, 50-70 parts by mass of Mg-(1.5-3wt.%) RE alloy powder, and 1-5 parts by mass of Mg-15wt.% Mn alloy powder.

[0042] It should be noted that Mg-(2-4wt.%)Zn alloy powder means that the mass content of Zn in the alloy powder is 2% to 4%, and the balance is Mg. Mg-(1.5-3wt.%)RE alloy powder means that the mass content of RE in the alloy powder is 1.5% to 3%, and the balance is Mg. Mg-15wt.%Mn alloy powder means that the mass content of Mn in the alloy powder is 15%, and the balance is Mg.

[0043] Furthermore, RE may be one or more of the rare earth elements Gd, Ce, La, Nd, and Y.

[0044] Step 3: Provide raw materials for preparing the transition layer: high Zn content magnesium alloy powder.

[0045] The high Zn content magnesium alloy powder includes 80-90 parts by mass of Mg-(2-4wt.%)Zn alloy powder and 10-20 parts by mass of Mg-15wt.%Mn alloy powder.

[0046] The transition layer made of high-Zn magnesium alloy powder is used to connect the outer layer and the inner layer, so that the Mg-Sn / Mg-Zn / Mg-RE alloy interdiffusion layer can be formed at the interface, avoiding the generation of brittle MgSnRE phase, thereby forming a reliable metallurgical bond at the interface of the inner and outer layers, avoiding the occurrence of cracking, etc. The controllable preparation of the inner and outer layers and the transition layer can synergistically obtain the comprehensive mechanical properties of high corrosion resistance and high strength and toughness.

[0047] It should be noted that steps 1 to 3 are only for the convenience of description and are not intended to limit the order of the steps. The above raw materials can be prepared simultaneously or one after another, and only need to be prepared in advance.

[0048] Step 4: Lay the above-mentioned high Sn content magnesium alloy powder, high Zn content magnesium alloy powder and high RE content magnesium alloy powder on the outer layer, transition layer and inner layer of the cylindrical mold cavity respectively, and then perform molding.

[0049] It can be understood that the high Sn content magnesium alloy powder is laid in the outer layer of the cylindrical mold cavity, the high RE content magnesium alloy powder is laid in the inner layer of the cylindrical mold cavity, and the high Zn content magnesium alloy powder is laid in the transition layer corresponding to the outer layer and the inner layer.

[0050] Furthermore, the thickness of the pure magnesium foil is 0.3-0.8 mm, the radial width of the magnesium alloy powder with high Sn content is 20-40 mm, the radial width of the magnesium alloy powder with high Zn content is 3-10 mm, and the radial width of the magnesium alloy powder with high RE content is 40-100 mm.

[0051] Furthermore, the molding pressure is 60MPa to 100MPa.

[0052] Step 5: The cylindrical powder blank after demoulding is subjected to vacuum hot pressing sintering and extrusion deformation to obtain a magnesium alloy deformed material.

[0053] It should be noted that the vacuum hot pressing sintering temperature is 480° C. to 550° C., the time is 2 to 3 hours, and the pressure is 10 to 50 MPa.

[0054] Furthermore, the extrusion deformation temperature is 250°C to 400°C, and the extrusion ratio is 5 to 15.

[0055] Step six: subjecting the magnesium alloy deformed material obtained above to rolling deformation and annealing heat treatment to obtain a dual-texture corrosion-resistant magnesium alloy material.

[0056] It should be noted that the rolling deformation temperature is 20° C. to 100° C., the rolling deformation amount is 5% to 10%, and the rolling direction is parallel to the extrusion direction.

[0057] Furthermore, the annealing heat treatment is performed at a temperature of 200° C. to 350° C. and for a time of 30 to 240 minutes.

[0058] The magnesium alloy material produced by the above method has dual texture characteristics, as well as excellent properties such as high corrosion resistance, high strength and toughness, and high interface bonding strength. It can meet the requirements of engineering application fields such as aerospace, transportation, and 3C communication electronic products.

[0059] The following are specific embodiments.

[0060] Example 1

[0061] (1) Providing a magnesium alloy powder with a high Sn content: 70 parts of Mg-7wt.% Sn alloy powder and 30 parts of Mg-3wt.% Zn alloy powder are mixed uniformly.

[0062] (2) Providing magnesium alloy powder with high RE content: wherein RE is selected from Gd element, 70 parts of Mg-2wt.% Gd alloy powder, 25 parts of Mg-4wt.% Zn alloy powder, and 5 parts of Mg-15wt.% Mn alloy powder are mixed evenly.

[0063] (3) Providing high Zn content magnesium alloy powder: 80 parts of Mg-4wt.% Zn alloy powder and 20 parts of Mg-15wt.% Mn alloy powder are mixed evenly.

[0064] (4) The above-mentioned high Sn content magnesium alloy powder, high Zn content magnesium alloy powder and high Gd content magnesium alloy powder are laid on the outer layer, middle transition layer and inner layer of the cylindrical mold cavity respectively, and pure magnesium foil is arranged between adjacent layers. The thickness of the pure magnesium foil is 0.3mm, the radial width of the laying of the high Sn content magnesium alloy powder is 20mm, the radial width of the laying of the high Zn content magnesium alloy powder is 10mm, and the radial width of the laying of the high Gd content magnesium alloy powder is 80mm. After the powder is laid, it is molded at a pressure of 80MPa.

[0065] (5) After demolding, vacuum hot pressing sintering is performed at a temperature of 500°C, a time of 2 hours, and a pressure of 30 MPa. After the sintered blank is taken out, extrusion deformation is performed at a temperature of 400°C and an extrusion ratio of 10.

[0066] (6) The extruded deformed material is subjected to rolling deformation and annealing heat treatment, the rolling deformation temperature is 20°C, the rolling deformation amount is 8%, the rolling direction is parallel to the extrusion direction, and the rolled plate is subjected to annealing heat treatment, the annealing temperature is 350°C, and the time is 90 minutes. Finally, a dual-texture corrosion-resistant magnesium alloy material is obtained.

[0067] After testing, the outer layer of the magnesium alloy material prepared in Example 1 is a cylindrical texture with a texture strength of 6.5 mrd; the inner layer is a rare earth texture with a texture strength of 4.5 mrd. Figure 2 As shown in Figure 2, the corrosion current density measured in 3.5wt.% NaCl solution is 2.62×10 -2 mA / cm 2 , the material has good corrosion resistance.

[0068] Comparative Example 1

[0069] Comparative Example 1 is substantially the same as Example 1, except that the preparation of the transition layer is omitted in Comparative Example 1, that is, high Zn content magnesium alloy powder and pure magnesium foil are not added between the high Sn content magnesium alloy powder and the high RE content magnesium alloy powder.

[0070] After testing, the material of comparative example 1 had cracks opening at the junction of the inner and outer layers during the extrusion process, and the extruded profile showed delamination of the inner and outer layers. Microstructural observation revealed that a large number of fireworks-like MgSnGd ternary phases were formed between the inner and outer layers, and a large number of cracks existed in the phases, such as Figure 3 As shown in the figure, due to the delamination of the material, subsequent rolling deformation and corrosion resistance testing were impossible.

[0071] Example 2

[0072] (1) Providing a magnesium alloy powder with a high Sn content: 90 parts of Mg-5wt.% Sn alloy powder and 10 parts of Mg-3wt.% Zn alloy powder are mixed evenly.

[0073] (2) Providing magnesium alloy powder with high RE content: wherein RE is selected from Nd element, 70 parts of Mg-1.5wt.% Gd alloy powder, 25 parts of Mg-2wt.% Zn alloy powder, and 5 parts of Mg-15wt.% Mn alloy powder are mixed evenly.

[0074] (3) Providing high Zn content magnesium alloy powder: 90 parts of Mg-2wt.% Zn alloy powder and 10 parts of Mg-15wt.% Mn alloy powder are mixed evenly.

[0075] (4) The above-mentioned high Sn content magnesium alloy powder, high Zn content magnesium alloy powder and high Nd content magnesium alloy powder are laid on the outer layer, middle transition layer and inner layer of the cylindrical mold cavity respectively, and pure magnesium foil is arranged between adjacent layers. The thickness of the pure magnesium foil is 0.5 mm, the radial width of the laying of the high Sn content magnesium alloy powder is 40 mm, the radial width of the laying of the high Zn content magnesium alloy powder is 8 mm, and the radial width of the laying of the high Gd content magnesium alloy powder is 100 mm. After the powder is laid, it is molded at a pressure of 100 MPa.

[0076] (5) After demolding, vacuum hot pressing sintering is performed at a temperature of 480°C, a time of 3 hours, and a pressure of 50 MPa. After the sintered blank is taken out, extrusion deformation is performed again at a temperature of 300°C and an extrusion ratio of 5.

[0077] (6) The extruded deformed material is subjected to rolling deformation and annealing heat treatment, the rolling deformation temperature is 20°C, the rolling deformation amount is 5%, the rolling direction is parallel to the extrusion direction, and the rolled plate is subjected to annealing heat treatment, the annealing temperature is 200°C, and the time is 240 minutes. Finally, a dual-texture corrosion-resistant magnesium alloy material is obtained.

[0078] After testing, the outer layer of the magnesium alloy material prepared in Example 2 is a cylindrical texture with a texture strength of 7.2 mrd; the inner layer is a rare earth texture with a texture strength of 4.8 mrd; the corrosion current density measured in a 3.5wt.% NaCl solution is 2.83×10 -2 mA / cm 2 , the material has good corrosion resistance.

[0079] Comparative Example 2

[0080] Comparative Example 2 is substantially the same as Example 2, except that the rolling process is omitted in Comparative Example 2, that is, annealing is performed directly after vacuum hot pressing sintering and extrusion deformation without rolling deformation.

[0081] After testing, the outer layer of the magnesium alloy material prepared in Comparative Example 2 is a basal fiber texture with a texture strength of 8.7 mrd; the inner layer is a rare earth texture with a texture strength of 4.8 mrd; the corrosion current density measured in a 3.5wt.% NaCl solution is 5.98×10 -2 mA / cm 2 , the corrosion resistance of the material is poor.

[0082] Example 3

[0083] (1) Providing magnesium alloy powder with high Sn content: 70 parts of Mg-6wt.% Sn alloy powder and 30 parts of Mg-3wt.% Zn alloy powder are mixed evenly.

[0084] (2) Providing magnesium alloy powder with high RE content: wherein RE is selected from Y element, 50 parts of Mg-3wt.% Y alloy powder, 45 parts of Mg-3wt.% Zn alloy powder, and 5 parts of Mg-15wt.% Mn alloy powder are mixed evenly.

[0085] (3) Providing high Zn content magnesium alloy powder: 80 parts of Mg-3wt.% Zn alloy powder and 20 parts of Mg-15wt.% Mn alloy powder are mixed evenly.

[0086] (4) The above-mentioned high Sn content magnesium alloy powder, high Zn content magnesium alloy powder and high Y content magnesium alloy powder are laid on the outer layer, middle transition layer and inner layer of the cylindrical mold cavity respectively, and pure magnesium foil is arranged between adjacent layers. The thickness of the pure magnesium foil is 0.8 mm, the radial width of the laying of the high Sn content magnesium alloy powder is 30 mm, the radial width of the laying of the high Zn content magnesium alloy powder is 3 mm, and the radial width of the laying of the high Y content magnesium alloy powder is 40 mm. After the powder is laid, it is molded at a pressure of 60 MPa.

[0087] (5) After demolding, vacuum hot pressing sintering is performed at a temperature of 550°C, a time of 2 hours, and a pressure of 10 MPa. After the sintered blank is taken out, extrusion deformation is performed again at a temperature of 350°C and an extrusion ratio of 15.

[0088] (6) The extruded deformed material is subjected to rolling deformation and annealing heat treatment, the rolling deformation temperature is 100°C, the rolling deformation amount is 10%, the rolling direction is parallel to the extrusion direction, and the rolled plate is subjected to annealing heat treatment, the annealing temperature is 300°C, and the time is 90 minutes. Finally, a dual-texture corrosion-resistant magnesium alloy material is obtained.

[0089] After testing, the outer layer of the magnesium alloy material prepared in Example 3 is a cylindrical texture with a texture strength of 9.45 mrd; the inner layer is a rare earth texture with a texture strength of 3.9 mrd; the corrosion current density measured in a 3.5wt.% NaCl solution is 2.71×10 -2 mA / cm2 , the material has good corrosion resistance.

[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a dual-texture corrosion-resistant magnesium alloy material, characterized in that: The specific preparation method comprises the following steps: Step 1, providing a raw material high Sn content magnesium alloy powder for preparing the outer layer of the material, which is mixed with 70 to 90 parts by mass of Mg-(5-7wt.%) Sn alloy powder and 10 to 30 parts by mass of Mg-(2-4wt.%) Zn alloy powder; Step 2, providing a raw material high RE content magnesium alloy powder for preparing the inner layer of the material, which is mixed with 25 to 45 parts by mass of Mg-(2-4wt.%) Zn alloy powder and 50 to 70 parts by mass of Mg-(1.5-3wt.%) RE alloy powder, and 1 to 5 parts by mass of Mg-15wt.% Mn alloy powder, wherein RE is one or more of the rare earth elements Gd, Ce, La, Nd, and Y; Step 3, providing a raw material high Zn content magnesium alloy powder for preparing the transition layer, which is mixed with 80-90 parts by mass of Mg-(2-4wt.%)Zn alloy powder and 10-20 parts by mass of Mg-15wt.%Mn alloy powder; Step four, laying the high Sn content magnesium alloy powder, high Zn content magnesium alloy powder, and high RE content magnesium alloy powder on the outer layer, transition layer, and inner layer of the cylindrical mold cavity respectively, and obtaining the dual-texture corrosion-resistant magnesium alloy material through molding, vacuum hot pressing sintering, extrusion and rolling deformation, and annealing heat treatment.

2. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to claim 1, characterized in that: Pure magnesium foil is provided between the laying positions of the magnesium alloy powder with high Sn content and the magnesium alloy powder with high Zn content, and between the laying positions of the magnesium alloy powder with high Zn content and the magnesium alloy powder with high RE content, respectively, and the thickness of the foil is 0.3-0.8 mm.

3. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to claim 1, characterized in that: The radial width of the magnesium alloy powder with high Sn content is 20-40 mm, the radial width of the magnesium alloy powder with high Zn content is 3-10 mm, and the radial width of the magnesium alloy powder with high RE content is 40-100 mm.

4. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to any one of claims 1 to 3, characterized in that: The molding pressure is 60MPa to 100MPa.

5. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to any one of claims 1 to 3, characterized in that: The vacuum hot pressing sintering is performed at a temperature of 480° C. to 550° C., for 2 to 3 hours, and at a pressure of 10 to 50 MPa.

6. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to any one of claims 1 to 3, characterized in that: The extrusion deformation temperature is 300° C. to 400° C., and the extrusion ratio is 5 to 15.

7. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to any one of claims 1 to 3, characterized in that: The rolling deformation temperature is 20° C. to 100° C., the rolling deformation amount is 5% to 10%, and the rolling direction is parallel to the extrusion direction.

8. The method for preparing a dual-texture corrosion-resistant magnesium alloy material according to any one of claims 1 to 3, characterized in that: The annealing heat treatment is performed at a temperature of 200° C. to 400° C. and for a time of 30 to 240 minutes.

Citation Information

Patent Citations

  • Preparation method for magnesium alloy plate with four-peak non-basal texture characteristics

    CN113073275A

  • High-formability magnesium alloy double-layer composite plate containing rare earth yttrium and preparation method of high-formability magnesium alloy double-layer composite plate

    CN114179457A